The Vounous Jars Revisited - Ross, James F. (Bulletin of ASOR, 1994)
An imported jar found in Tomb 164B at Vounous in Cyprus is shown to be from Palestine, dating to either very late EB III or early EB IV. Other jars from Tombs 64 and 68 are somewhat later, but still in EB IV, probably from Syria. The evidence of these imports supports raising the chronology of the periods represented by the tombs, respectively EC I and II and MC I.